2020
DOI: 10.3390/cancers12102871
|View full text |Cite
|
Sign up to set email alerts
|

High G2M Pathway Score Pancreatic Cancer is Associated with Worse Survival, Particularly after Margin-Positive (R1 or R2) Resection

Abstract: Pancreatic cancer is highly mortal due to uncontrolled cell proliferation. The G2M checkpoint pathway is an essential part of the cell cycle. We hypothesized that a high G2M pathway score is associated with cell proliferation and worse survival in pancreatic cancer patients. Gene set variation analysis using the Hallmark G2M checkpoint gene set was used as a score to analyze a total of 390 human pancreatic cancer patients from 3 cohorts (TCGA, GSE62452, GSE57495). High G2M score tumors enriched other cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 74 publications
2
39
0
Order By: Relevance
“…In order to quantify the activity of the DNA repair pathway, we defined the DNA repair pathway score based on the gene set variation analysis (GSVA) score of the Molecular Signatures Database Hallmark DNA repair gene set ( Table S1 ), using the methodology we previously reported [ 4 , 5 , 9 , 10 , 11 ]. The DNA repair score correlated with expression of BRCA1 and BRCA2, arguably the most clinically significant DNA repair genes associated with cancer prognosis and treatment sensitivity ( Figure S1 ; Spearman’s rank correlation coefficient (r) = 0.576 ( p < 0.01) and 0.471 ( p < 0.01), respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to quantify the activity of the DNA repair pathway, we defined the DNA repair pathway score based on the gene set variation analysis (GSVA) score of the Molecular Signatures Database Hallmark DNA repair gene set ( Table S1 ), using the methodology we previously reported [ 4 , 5 , 9 , 10 , 11 ]. The DNA repair score correlated with expression of BRCA1 and BRCA2, arguably the most clinically significant DNA repair genes associated with cancer prognosis and treatment sensitivity ( Figure S1 ; Spearman’s rank correlation coefficient (r) = 0.576 ( p < 0.01) and 0.471 ( p < 0.01), respectively).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the association of several pathways with clinical outcomes in various cancers. The G2M checkpoint pathway score identified poor survival in pancreatic and breast cancer patients, and it demonstrated potential as a predictive biomarker for chemotherapy in breast cancer [ 4 , 5 ]. The E2F target pathway score also demonstrated potential as a predictive biomarker for neoadjuvant therapy in breast cancer [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yamazaki et al reported that epithelial–mesenchymal transition (EMT) activity in PC is a promising prognostic biomarker. Our group reported that high activity of the G2M checkpoint pathway [ 5 ] and lympho-vascular invasion [ 6 ] is associated with worse survival. In contrast, the abundance of mature blood vessels [ 7 ] and fibroblasts in PC [ 8 ] is associated with better survival.…”
Section: Introductionmentioning
confidence: 99%